Clinical and electroencephalographic features of children with eating-induced reflex epilepsy: A report of three cases - LIANG Jingjing, NIU Yue, CUI Ya'nan, QIN Jiong, YANG Zhixian (精准医学杂志, 2024)
Objective To investigate the clinical and electroencephalographic (EEG) features of children with eating-induced reflex epilepsy. Methods A retrospective analysis was performed for the clinical features, EEG findings, treatment, and prognosis of three children with eating-induced reflex epilepsy who attended Department of Pediatrics in our hospital from 2014 to 2024. Results There were two boys among the three children. Two children had normal intellectual development before the onset of the disease, while one was diagnosed with intellectual disability. All three children had normal cranial MRI results, and whole-exome genetic testing and copy number variation testing were performed for two children and their families, which yielded negative results. In case 1, the child had focal seizures and later developed into focal secondary bilateral tonic-clonic seizures, and EEG monitoring showed bilateral Rolandic discharges in the interictal period, but without eating-induced seizures. In case 2, the child had focal epileptic spasms during wakefulness and generalized myoclonic seizures during sleep, and EEG monitoring showed the coexistence of multifocal discharges and generalized discharges in the interictal period, drinking water induced three clusters of predominantly right-sided generalized multiphase slow waves with epileptic spasms, as well as several spontaneous generalized myo-clonic seizures during sleep. In case 3, the child had coexistence of focal epileptic spasms and generalized tonic seizures, and EEG monitoring showed the coexistence of multifocal discharges and generalized discharges, eating induced a cluster of predominantly left posterior multiphase slow waves with epileptic spasms. All three children received more than two anti-seizure medications (ASMs) and failed to achieve the control of seizures, and they presented with varying degrees of intellectual disability after disease onset. Conclusion Eating-induced reflex epilepsy is slightly more common in boys and is often accompanied by intellectual disability after disease onset. The coexistence of spontaneous seizures and induced seizures is often observed in this disease, with epileptic spasms being the more common type of eating-induced seizures. EEG manifestations in the interictal period include focal discharges, generalized discharges, or the coexistence of both types of discharges. ASMs have a poor therapeutic effect on this disease.